Public health policies in dental traumatology: A call for action! - Brandini, Daniela Atili [UNESP]; Carvalho de Souza Cantão, Ana Beatriz; Levin, Liran (Wiley, 2024)
Traumatic dental injuries (TDI) are a prevalent public health concern, requiring preventive measures as well as timely and appropriate interventions to prevent adverse outcomes and optimize patients' prognosis. Although dental trauma injuries require prompt clinical intervention, some challenges persist in effectively managing these injuries. In dental traumatology, the implementation of public health policies assumes critical importance, these policies play an important role in addressing preventive measures and mitigating the repercussions of TDI. This review aims to emphasize the importance of developing comprehensive public health policies in dental traumatology, recognizing the strategic importance of this approach and its benefits. By proactively addressing issues associated with dental injuries, these policies have extensive implications for individual quality of life and public health in general. Furthermore, this review will present a suggested structured framework for the development of public health policies, encompassing key domains including prevention, intervention, and education in dental traumatology. The creation and implementation of these policies will address dental trauma through prevention programs, research, and development, and will provide a significant step toward enhancing the well-being of the population and dental trauma victims' prognosis promoting a more resilient healthcare system.
Keywords: education; maxillofacial injuries; oral health; oral injuries; public health; traumatic dental injuries